The song of the Brazilian population of Humpback Whale Megaptera novaeangliae, in the year 2000: individual song variations and possible implications - Arraut,Eduardo M.; Vielliard,Jacques M.E. (Academia Brasileira de Ciências, 2004)
The song of the Brazilian population of the Humpback Whale Megaptera novaeangliae was studied in its breeding and calving ground, the Abrolhos Bank, Bahia, Brazil, from July to November 2000. Aural and spectral analyses of digital recordings were completed for approximately 20 song cycles, totaling 5 hours of song from 10 different recording events. We identified 24 note types, organized in five themes. All songs presented the same themes and the order in which they were sung did not vary. We registered the appearance of a note type and the disappearance of a phrase ending, which indicate that the song changed as the season progressed. Moreover, we detected individual variation in the way singers performed certain complex note types. As songs are transmitted culturally, it is likely that singers have different abilities to compose and/or learn new notes. If, as it has been previously suggested, 'new' songs are preferred to 'old' ones, these more able singers will be sending out information about their learning abilities that could be used by other whales to decide whether or not to interact with them.